2014
DOI: 10.1586/14737140.2014.965688
|View full text |Cite
|
Sign up to set email alerts
|

Biopsy sampling and histopathological markers for diagnosis of prostate cancer

Abstract: Prostate cancer is one of the most common malignant tumors and a leading cause of cancer-related morbidity and mortality. Irrespective of the method that allows for risk stratification of prostate cancer suspects, diagnosis relies on tissue sampling through prostate biopsy and subsequent histopathological evaluation. This provides critical information about disease aggressiveness, which is required for adequate patient management. Prostate biopsy methods have significantly evolved over the years, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 113 publications
0
2
1
Order By: Relevance
“…The mean preoperative total prostate specific antigen (TPSA) in this study was as higher as what has been documented in large number of studies done in developing countries even thoughit was not 14,15,16 exactly similar.…”
Section: Figure 3shows Extraprostatic Extension (Epe) Ofcontrasting
confidence: 60%
“…The mean preoperative total prostate specific antigen (TPSA) in this study was as higher as what has been documented in large number of studies done in developing countries even thoughit was not 14,15,16 exactly similar.…”
Section: Figure 3shows Extraprostatic Extension (Epe) Ofcontrasting
confidence: 60%
“…A reclassification rate of 10% to 30% has been reported during the follow-up of patients on active surveillance [3; 12; 16]. This is thought to be mainly due to under sampling of significant tumors at initial biopsy rather than progression of low-risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 20–40% of patients who are considered to have low-risk disease based on a random prostate biopsy are subsequently upstaged if a second (confirmatory) biopsy is performed [313]. This is not surprising considering reports showing that a standard prostate biopsy only samples approximately 1% of prostate tissue [1416]. Studies have also shown that a clinical workup strategy, which includes prostate magnetic resonance imaging (MRI), aids the prediction of the results of confirmatory biopsy findings, however the results published so far demonstrate wide space for improvement in the use of MRI for this purpose [7; 1720].…”
Section: Introductionmentioning
confidence: 99%